Interculturality in English Language Teaching - Leão, Ana (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
UNESCO and the Council of Europe have been working on approaches in education to develop tolerance, respect for cultural diversity, and intercultural dialogue. Portugal, like many other countries, has established the intercultural domain as a goal in the foreign language curricula. Nonetheless, this commitment to developing intercultural dialogue has been questioned by researchers worldwide who consider that action is needed to effectively promote intercultural competence in the classroom. In this article, I examine teachers’ perceptions and beliefs about intercultural communicative competence in a cluster of schools in Portugal and the evidence shows that although foreign language teachers are willing to comply with an intercultural dimension, their profile is more compatible with that of a traditional foreign language teacher, rather than with a foreign language teacher who promotes intercultural communicative competence.